2015
DOI: 10.14419/ijsw.v3i1.4039
|View full text |Cite
|
Sign up to set email alerts
|

Sound velocities and thermal properties of BX (X=As, Sb) compounds

Abstract: The sound velocities and thermal properties of Boron-Arsenide (BAs) and Boron-Antimonide (BSb) materials have been predicted with the help of the empirical elastic constants which are taken from our previous work which is accepted to publication in International Journal of Scientific World. The longitudinal, transverse and average elastic wave velocities, the Debye temperature, the melting temperature, the thermal conductivity, the linear thermal expansion coefficient and finally the Grüneisen parameter are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 29 publications
3
27
4
Order By: Relevance
“…Eq. (7) ); the predicted value of the Debye temperature of BSb material is equal to 415.81 K; this value is in general in agreement with the value 456.07 K obtained in our previous work [6]. The deviation between our value and this cited in the Ref.…”
Section: Debye Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…Eq. (7) ); the predicted value of the Debye temperature of BSb material is equal to 415.81 K; this value is in general in agreement with the value 456.07 K obtained in our previous work [6]. The deviation between our value and this cited in the Ref.…”
Section: Debye Temperaturesupporting
confidence: 92%
“…Knowledge of different thermodynamic properties such as Debye temperature helps engineers in the improvement of the manufacturing of the semiconductor devices by good selecting of the appropriate materials [2]. And due to technological importance of II-VI and III-V semiconductors, several experimental and theoretical works [4][5][6][7][8][9] on their electronic, optical, mechanical and thermal properties were published. The present work aims to establish simple empirical expressions between the Debye temperature and the bond length, and between the melting point and the bond length for II-VI and III-V semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained value of Tm was calculated, it is around 1653.2 K. These two values are slightly lower than the results of our previous works [6], [9] (Table 3) and references therein.…”
Section: Debye Temperature and Melting Temperaturecontrasting
confidence: 62%
“…In our very recent work [5], a quasi-linear relationship was obtained between the high-frequency and static dielectric constants in some II-VI and III-V materials. Some other physical quantities such as: Knoop microhardness, homopolar and heteropolar energies, thermal conductivity, and melting point of boron based materials (BAs, and BSb) are also the object of other our recent works [6][7][8]. Using first principles calculations, the structural phase transition, elastic constants, sound velocity, and Debye temperature of BAs were studied under pressure up to 125 GPa [9].…”
Section: Introductionmentioning
confidence: 99%
“…They have found that the electronic properties of these semiconductor materials are different from those of other III-V compounds (the direct band gap pressure coefficient is nearly independent of the anion substitutions). In our recent work [5][6][7], several physical quantities such as: cohesive energy, elastic constants, Kleinman parameter, Cauchy's discrepancy in elastic constant, Cauchy's coefficient, Born ratio, Knoop micro hardness, homopolar and heteropolar energies, the bonding-anti bonding energy gap, the covalency and the sound velocity of BSb semiconductor were studied. In another recent work [8], we have established a quantitative form of the linear correlation between the high-frequency and static dielectric constants in A N B 8-N (N = 2, 3) tetrahedral semiconductors, where we found a quasi-linear relationship between the high-frequency and static dielectric constants for II-VI and III-V binary materials.…”
Section: Introductionmentioning
confidence: 99%